Artificial time inconsistency as a remedy for the race to the bottom - Alfons J. Weichenrieder; Oliver Busch (Center for Economic Studies and ifo Institute (CESifo), 2005)
A long-standing concern in the literature has been that household mobility implies a serious threat to the viability of redistributive taxation. This paper considers the effects of deferred integration of migrants into the redistributive system of the target country. In a model of symmetric regions, deferred integration introduces a time consistency problem into governments' tax plans which reduces a region's incentive to undercut other regions' tax rates and can bring tax competition to a halt. On the one hand, rich migrants cease to benefit from the lower tax rate in the current period. On the other hand, the region's promise of a continuing low rate in the future is not credible. We also explore the case where poor recipients of social assistance are mobile while the rich are immobile.
Keywords: H25; 330; tax competition; federalism; mobility; social assistance; time consistency; Steuerwettbewerb; Einkommensumverteilung; Binnenwanderung; Soziale Integration; Zeitkonsistenz; Theorie